The effectiveness of a program based on the aesthetic values of Arabic calligraphy to develop artistic creativity skills among students of Faculty of Fine Arts at Al-Aqsa University In Gaza Strip - Palestine/2023 (Journal of the College of Basic Education, 2023)
The purpose of the study was to evaluate the effectiveness of a program based on Arabic calligraphy's aesthetic value in helping female Al-Aqsa University Faculty of Fine Arts students develop their artistic creativity.The study sample of female College of Fine Arts students, recorders, and Arabic calligraphy was chosen at random and had (20) artistic knowledge of the aesthetic values, of Arabic calling. For this purpose, the researcher used the constructivist approach to build the program. The semi-transient approach was used to display the quasi-design. Was scientific research used to determine the two tools' validity?It is presented to a group of specialized arbitrators to accomplish this.The following statistical techniques were employed to respond to the study's questions and support its hypothesis